Phytophthora Management in Citrus Nurseries - Megan M. Dewdney; Jamie D. Burrow (EDIS)
Check out the new fact sheet about Phytopthora Management in Citrus Nurseries. A great on-hand resource, this fact sheet covers sanitation practices, tools, and potting media for citrus nurseries. It also illustrates correct and incorrect practices and provides information about disinfectants and chemicals to use. Written by Megan M. Dewdney and Jamie D. Burrow, and published by the Plant Pathology Department, January 2016.